Local Forages from Biak Utara as Goat Feeds: Relationships between Nutrient Composition, Fermentation, and In Vitro Digestibility - Tethool, Rina M.E.S.; Saragih, Evi Warintan; Santoso, Budi (Faculty of Animal Science, Universitas Brawijaya, 2025)
This study aimed to evaluate the chemical composition, in vitro fermentation characteristics, and nutrient digestibility of local forages from Biak Utara District, Biak Numfor Regency, Papua. Eleven forage species commonly consumed by ruminants were collected, combined with elephant grass (Pennisetum purpureum) at a ratio of 64.2:35.8, and incubated in vitro for 48 h in cattle rumen fluid. The chemical composition, pH, ammonia-nitrogen (NH?-N) content, volatile fatty acid (VFA) content, gas production, methane (CH?) content, and in vitro digestibility of dry matter (DMD) and organic matter (OMD) were determined. The data were analysed via ANOVA followed by Duncan’s multiple range test. The results revealed wide variation in the crude protein (13.0–25.2%) and fibre fractions (NDF 33.2–61.6%; ADF 32.0–53.8%; hemicellulose 1.2–19.3%), which significantly affected fermentation characteristics and nutrient digestibility. The NH?-N concentration (29.5–40.9 mg/100 ml) exceeded the minimum threshold required for microbial protein synthesis. The total VFA concentration ranged from 61.3 to 81.2 mM, with higher values in forages with lower fibre fractions. Total gas and CH? production also varied, with the highest values observed in combinations with Garcinia dulcis and Morinda citrifolia. These combinations also had the highest DMD and OMD values (63.2% and 62.4%, respectively), whereas Ficus recemosa yielded the lowest values. In conclusion, the nutritional quality and fermentability of local forages are strongly influenced by the balance between the crude protein and fibre fractions. Forages with lower NDF and ADF contents and adequate protein levels improved digestibility and fermentation, indicating their potential to increase ruminant productivity in Biak Numfor Regency.